2016
DOI: 10.1016/j.ijid.2016.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Application of Pharmacodynamic Profiling for the Selection of Optimal β-lactam Regimens in a Large University Hospital

Abstract: The pharmacodynamic profiling undertaken in the current study provides insights that allow prescribers to select more appropriate empirical antibiotic regimens for the treatment of infection caused by these common GNB pathogens at this Thai hospital. While higher doses and PI of β-lactams improve exposures against EC, KP and PA, this approach will not sufficiently enhance their potency against AB, thus alternative therapies should be considered for this organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The purpose of this mini review was to briefly survey the techniques and decisions researchers made while performing cefepime PTA. Therefore, only the first 20 titles were reviewed, of which 14 met the inclusion criteria of a PTA study, with at least one evaluation of cefepime alone in adult patients ( Table 1 ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. A study by Das et al was excluded because cefepime was studied in combination with a novel beta-lactamase inhibitor, changing the risk benefit from cefepime alone [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of this mini review was to briefly survey the techniques and decisions researchers made while performing cefepime PTA. Therefore, only the first 20 titles were reviewed, of which 14 met the inclusion criteria of a PTA study, with at least one evaluation of cefepime alone in adult patients ( Table 1 ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. A study by Das et al was excluded because cefepime was studied in combination with a novel beta-lactamase inhibitor, changing the risk benefit from cefepime alone [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The MIC of interest was generally set at 8 mg/dL, consistent with the breakpoint defined by the Clinical and Laboratory Standards Institute against pseudomonas aeruginosa [ 35 ]. Success was commonly defined as PTA > 90% against a given MIC; however, some authors defined success as CFR > 90% against an observed MIC distribution [ 18 , 20 , 21 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…As two recent studies have suggested, the carbapenem MIC might influence the clinical outcome in patients with Gram-negative bacterial infections (31,32); therefore, optimization of the doripenem dosing regimen according to the MIC for the causative organism is required. In this context, the application of PK profiles to adjust the dosing regimen and the mode of administration is particularly important for infections caused by pathogens with decreased in vitro susceptibility and higher MICs, such as Pseudomonas aeruginosa (33). From our point of view, local susceptibility data could be precious.…”
Section: Discussionmentioning
confidence: 99%